2019
DOI: 10.3889/oamjms.2019.326
|View full text |Cite
|
Sign up to set email alerts
|

Glial Fibrillary Acidic Protein Serum Level as a Predictor of Clinical Outcome in Ischemic Stroke

Abstract: BACKGROUND: Glial Fibrillary Acidic Protein (GFAP) is a protein produced by astrocytes in response to brain injury, which then penetrates the cerebrospinal fluid and the blood stream. AIM: We sought to determine whether GFAP serum level in acute ischemic stroke could predict clinical outcome. METHODS: As much as 64 patients with first-ever ischemic stroke had their GFAP serum level measured at 72 hours after onset. The National Institute of Health Stroke Scale (NIHSS) was assessed during the 72 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…A further mechanistic study by Raza et al demonstrated that naringenin enhanced the depleted antioxidant markers, SOD and GSH. NF-κB-mediated pro-inflammatory factors including COX-2, iNOS, IL-1β as well as TNF-α were significantly alleviated in the naringenin pre-supplementation group [154]. The expression of GFAP and microglia (Iba-1) were noticeably mitigated in naringenin pre-treated group as compared to MCAO group [155].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A further mechanistic study by Raza et al demonstrated that naringenin enhanced the depleted antioxidant markers, SOD and GSH. NF-κB-mediated pro-inflammatory factors including COX-2, iNOS, IL-1β as well as TNF-α were significantly alleviated in the naringenin pre-supplementation group [154]. The expression of GFAP and microglia (Iba-1) were noticeably mitigated in naringenin pre-treated group as compared to MCAO group [155].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The expression of GFAP and microglia (Iba-1) were noticeably mitigated in naringenin pre-treated group as compared to MCAO group [155]. There is a close link between enhancing expression of glial fibrillary acidic protein (GFAP) and cerebral ischemia [154].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…6 Supported by research by Puspitasari et al which states there is a significant correlation between GFAP serum levels with stroke severity scale after 1 month of stroke onset. 7 This is different from the study conducted by Neila et al, which aims to determine the difference between blood sampling time and serum GFAP levels within 24 hours of onset in patients with ischemic stroke and hemorrhagic stroke, which shows that there was no significant difference in GFAP levels in samples <6 hours, 6-12 hours, and 12-24 hours in ischemic strokes and ICH strokes. 8 Factors that can influence GFAP include some cellular processes.…”
mentioning
confidence: 76%
“…The highest levels of GFAP were found in individuals diagnosed with skull fractures combined with ICH. 4 Additional research suggests that serum GFAP concentrations are an ideal biomarker to differentiate between various nontraumatic brain injuries such as ICH and acute ischemic stroke (AIS) with higher GFAP elevations presenting in cases where damage was more extensive 3,[5][6][7][8] Research on serum biomarkers has also shown that UCH-L1, an enzyme responsible for degradation in nerve cells, may also offer useful information in the classification and severity of brain injuries and has been associated with poor outcomes in individuals with both traumatic and nontraumatic brain injuries. 9 UCH-L1 is hypothesized to play a role in axon and neuronal repair by removing abnormal proteins that are present after injury.…”
Section: Introductionmentioning
confidence: 99%
“…The highest levels of GFAP were found in individuals diagnosed with skull fractures combined with ICH. 4 Additional research suggests that serum GFAP concentrations are an ideal biomarker to differentiate between various nontraumatic brain injuries such as ICH and acute ischemic stroke (AIS) with higher GFAP elevations presenting in cases where damage was more extensive 3, 5-8…”
Section: Introductionmentioning
confidence: 99%